High‐Water Marks: High Risk Appetites? Convex Compensation, Long Horizons, and Portfolio Choice - PANAGEAS, STAVROS; WESTERFIELD, MARK M. (Journal of Finance, 2009)
ABSTRACT We study the portfolio choice of hedge fund managers who are compensated by high‐water mark contracts. We find that even risk‐neutral managers do not place unbounded weights on risky assets, despite option‐like contracts. Instead, they place a constant fraction of funds in a mean‐variance efficient portfolio and the rest in the riskless asset, acting as would constant relative risk aversion (CRRA) investors. This result is a direct consequence of the in(de)finite horizon of the contract. We show that the risk‐seeking incentives of option‐like contracts rely on combining finite horizons and convex compensation schemes rather than on convexity alone.